"Wait for me until I Speak": Women's Tales in Ms. Jerusalem (National Library 803182) - Yassif, Eli (MiKAN, 2012)
The misogynic attitude to women in medieval Hebrew literature is well known by now. It has been studied, however, only in the learned literature of the time—legal documents, midrashim and commentaries, poetry, mystical treatises, and moral writings. All these were written documents put down by men and for men. Whether there is a way to hear the female voice in medieval Jewish culture, in which women did not write, is a question often asked, usually with a negative answer. Following studies in general folkloristics and feminist theory, I suggest that the female voice could be heard in the medium that was open to them—oral folk literature. As the major contributors to everyday life, women expressed themselves in various events, both intimate and more public, by telling stories and listening to them. In the early-sixteenth-century Ms. Jerusalem we find transcribed tales from a much earlier period (the thirteenth century) which express the ideas, feelings, and mentalities of broader strata of Jewish society, not just its male and learned members. Thirteen tales identifiable as 'women's tales' appear in this manuscript and are published and discussed here.